Do Maternal Quality of Life and Breastfeeding Difficulties Influence the Continuation of Exclusive Breastfeeding? - Forough Mortazavi; Seyed Abbas Mousavi; Reza Chaman; Ahmad Khosravi (International Journal of Pediatrics)
Objectives. This study was conducted to determine whether maternal quality of life (QOL) and breastfeeding difficulties influence the continuation of exclusive breastfeeding (EBF). Methods. In a survey, 358 consecutive pregnant women filled out a quality of life questionnaire in the third trimester of pregnancy and the breastfeeding experience scale at 4 weeks postpartum. We assessed breastfeeding practices every month up to 6 months postpartum. Results. Only 11.8% of women continued EBF at six months. Mothers who continued EBF at 2 and 4 months postpartum had better QOL in late pregnancy than mothers who discontinued it (P<0.05). There were no significant differences between the two groups in QOL scores at 6 months postpartum. Mothers who continued EBF at 2 months postpartum experienced less breastfeeding difficultties during one month postpartum than mothers who discontinued it (P<0.05). Conclusion. In attempts to promote EBF, mothers with poor QOL or breastfeeding difficulties in early postpartum should be identified and helped.